The remarkable propensity for the formation of C–H⋯π(chelate ring) interactions in the crystals of the first-row transition metal dithiocarbamates and the supramolecular architectures they sustain. - Tiekink, Edward R. T. * (Royal Society of Chemistry, 2020)
The Cambridge Crystallographic Database has been searched for the presence of intermolecular C– H⋯π(chelate ring) interactions, known to be stabilising, in the crystals of the first-row transition metal dithiocarbamates, i.e. containing anionic ligands of the type −S2CNR2, R = H, alkyl and aryl. A significant propensity to form C–H⋯π(chelate ring) interactions is noted, especially in crystals of nickel and copper dithiocarbamates. The participating hydrogen atoms are characterised as being near an electronegative atom/substituent encouraging their engagement in this supramolecular synthon. The survey shows that an open, square-planar geometry is not a prerequisite for a C–H⋯π(chelate ring) interaction but, allows, on average, more of these contacts leading to one- and two-dimensional architectures. It is concluded that a search for a C–H⋯π(chelate ring) supramolecular synthon should be included in any detailed analysis of the molecular packing of metal-containing crystals.